Optical in-situ sensors capture dissolved organic carbon (DOC) dynamics after prescribed fire in high-DOC forest watersheds - (:unkn) unknown (CSIRO PUBLISHING, 2019)
Fires alter terrestrial dissolved organic carbon (DOC) exports into water, making reliable post-fire DOC monitoring a crucial aspect of safeguarding drinking water supply. We evaluated DOC optical sensors in a pair of prescribed burned and unburned first-order watersheds at the Santee Experimental Forest, in the coastal plain forests of South Carolina, and the receiving second-order watershed during four post-fire storm DOC pulses. Median DOC concentrations were 30 and 23 mg L-1 in the burned and unburned watersheds following the first post-fire storm. Median DOC remained high during the second and third storms, but returned to pre-fire concentrations in the fourth storm. During the first three post-fire storms, sensor DOC load in the burned watershed was 1.22-fold higher than in the unburned watershed. Grab samples underestimated DOC loads compared with those calculated using the in-situ sensors, especially for the second-order watershed. After fitting sensor values with a locally weighted smoothing model, the adjusted sensor values were within 2 mg L-1 of the grab samples over the course of the study. Overall, we showed that prescribed fire can release DOC during the first few post-fire storms and that in-situ sensors have adequate sensitivity to capture storm-related DOC pulses in high-DOC forest watersheds.
Keywords: first-order watershed; forest management; prescribed burn; Santee Experimental Forest; South Carolina; WILDFIRE; MATTER; QUALITY; CATCHMENTS; DISCHARGE; EXPORT; TIME; FLOW